Revitalizing primary care is the key to people’s health in the post-COVID era - Jayanta Bhattacharya (Journal of Family Medicine and Primary Care)
Growing evidence shows that primary care–oriented systems achieve better health outcomes, more health equity, and lower costs. Despite this strong evidence, such care has been chronically underfunded. If a council focused on primary care had existed during the height of the coronavirus disease 2019 (COVID-19) pandemic, it could have helped rapidly mobilize primary care to address vaccine equity and shore up public health, particularly in rural and historically marginalized urban communities. We believe an infrastructure investment plan should include oversight, tools, and resources for rebuilding primary care. Researchers have tried to compare the number of deaths due to “neglected tropical diseases” and that due to COVID – total deaths in the former cases are greater than COVID deaths. We should take into consideration a few issues: (a) distinction between health (as a human right) and health care (as commodity), (b) “clinical health” and “public health,” (3) primary health care (as the backbone of public health) as well as community-based horizontal program NOT to be replaced by selective primary health care or GOBI or any disease-centered vertical program.